Digital Forensic Urgence in Analyzing Electronic Evidence for Evidence of Criminal Actions in Information and Electronic Transactions - Rivad Achmad Fahrezi Abdullah; Audyna Mayasari; Hijrah Adhyanti Mirzana (Journal of Development Research, 2023)
This study aims to determine the position of digital examination results as electronic evidence for proving criminal acts of information and electronic transactions. This research was conducted using normative research methods. which is done by researching library materials and judges' decisions then analyzing the materials which are methods or methods used in a legal research to find answers which will later become a prescription for the legal problems faced. The results of this study indicate that digital evidence in the form of information and electronic documents and has passed the digital forensic process is legal evidence, as stated in Article 5 paragraphs (1) and (2) of Law Number 19 of 2016 concerning Electronic Information and Transactions. . So that the position of electronic evidence from the results of digital forensic examinations as evidence of expert testimony and documentary evidence at the stage of investigation and proof in the trial process.